Overexpression of the wheat expansin gene TaEXPA2 improves oxidative stress tolerance in transgenic Arabidopsis plants - Chen, Yanhui (Plant physiology and biochemistry : PPB, 2018)
Copyright © 2018 Elsevier Masson SAS. All rights reserved.